Analisa Perbandingan Desain Panel Distribusi dengan Metode Computational Fluid Dynamics - Hutama, Adhi Setya; Kurniawan, Yohanes Hendra; Jati, Fajar Pranawa; Samodra, Yudha (Universitas Muhammadiyah Yogyakarta, 2023)
A distribution panel is a piece of equipment or device that consists of several electrical components that are arranged and arranged in such a way that they can distribute electrical power, and its use must guarantee security for users, so a Type-test is needed to determine the security of the distribution panel, one of the type-test tests is the temperature rise test. The temperature rise test was successfully carried out, but there are still problems, namely the heat distribution is unknown. The Computational Fluid Dynamics (CFD) method with flow simulation software can be used for heat transfer analysis in distribution panel systems, so that an ideal panel design is obtained to overcome overheating. The CFD analysis process is carried out by comparing 3 distribution panel designs, namely the first design using an exhaust fan, the second design with one output ventilation, and the design without an exhaust fan. Based on the results of the CFD analysis, the safest distribution panel results were obtained, namely the first design using an exhaust fan, the design with an exhaust fan experienced a temperature drop of 4°C compared to the design without an exhaust fan and the second design when viewed from surface 9.